2020
DOI: 10.14429/dlsj.5.15632
|View full text |Cite
|
Sign up to set email alerts
|

Seaweeds

Abstract: Seaweeds are microalgae growing in coastal regions and resistant to salinity. Seaweeds are rich resources of natural nutrients some of which cannot be obtained from terrestrial plants. Bioactive compounds of seaweeds such as sulphated polysaccharides, peptides, minerals, phlorotannins, carotenoids and sulfolipids have proven health benefits against various diseases. Traditionally, seaweeds are used as folk medicine for treating diseases like goiter, wounds, burns, rashes, inflammation, diabetes and also gainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Previous reports have shown that consumption of seaweeds may prevent the development of degenerative diseases and reduce their progression (Peñalver et al, 2020;Pereira & Valado, 2021). Seaweeds are functional foods and are a reservoir of naturally occurring biologically active compounds (Pandey et al, 2020). In our previous work on high performance liquid chromatography mass spectrometry (HPLC-MS) characterization of some seaweeds, we reported that E. The ability of KP and URL to reduce changes in mitochondria membrane potential in HepG2 cells may contribute to the observed induction of apoptosis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous reports have shown that consumption of seaweeds may prevent the development of degenerative diseases and reduce their progression (Peñalver et al, 2020;Pereira & Valado, 2021). Seaweeds are functional foods and are a reservoir of naturally occurring biologically active compounds (Pandey et al, 2020). In our previous work on high performance liquid chromatography mass spectrometry (HPLC-MS) characterization of some seaweeds, we reported that E. The ability of KP and URL to reduce changes in mitochondria membrane potential in HepG2 cells may contribute to the observed induction of apoptosis.…”
Section: Discussionmentioning
confidence: 91%
“…Previous reports have shown that consumption of seaweeds may prevent the development of degenerative diseases and reduce their progression (Peñalver et al, 2020; Pereira & Valado, 2021). Seaweeds are functional foods and are a reservoir of naturally occurring biologically active compounds (Pandey et al, 2020). In our previous work on high performance liquid chromatography mass spectrometry (HPLC‐MS) characterization of some seaweeds, we reported that E. maxima (KP) contain phlorotannins such as phloroglucinol and other phenolic compounds, including catechin, epicatechin‐3 glucoside, rutinose, vulgaxanthin, biochanin A and 1‐Caffeoyl‐4‐deoxyquinic acid (Olasehinde, Olaniran, & Okoh, 2019c).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocolloids like agar, alginates and carrageenan, and alkaloids, carotenoids, polyphenols, terpenes, tocopherols, laminarin, and fucoidan, among many others, have all been used as functional ingredients in bakery, dairy, fish, meat, and vegetable-based products [11,32]. Seaweed contains a considerable amount of protein that can be used to fulfil nutritional requirements or to treat malnutrition [9]. N. tenera (formerly P. tenera), N. yezoensis (formerly P. yezoensis), P. columbina (formerly P. columbina), and P. umbilicalis, Gracilaria spp., Sargassum wightii, Eucheuma spp., and many other species have been used in different varieties of seaweed-based foods and beverages such as wine, instant soup, noodles, jam, jelly, tea, porridge, soft cheese, sausages, among others, to enhance their nutritional value [32,174].…”
Section: Applicationsmentioning
confidence: 99%
“…(Peña‐Rodríguez et al., 2011). Moreover, seaweeds seem to also be a good source of diverse bioactive compounds, for instance peptides with antioxidant, antimicrobial and antiviral activities, among others (Holdt and Kraan, 2011; Pandey et al., 2020; Lomartire and Gonçalves, 2022).…”
Section: Introductionmentioning
confidence: 99%